Employment material in the Interior spaces of the directorates of queries in the city of Baghdad: آراء عبد الكريم حسين العبادي (Al-Academy, 2016)
this research concern with material function subject by using it in Baghdad education in formational places , because it considered as one of the most important spaces which needs a material presentation for the interior consistings that shares with prepairing the right mode for thos who use these spaces, regarding to that this research includes four chapters: Chapter one: concern with the research problem represented by the following question: can we use the material to place the hole spaces of information place ? So the aim of the research seems very obvious in functioning the material these places, and to take a close view on the importance of the research the theory , implementation and objective limits also concerning the terminology.Chapter two : deals with the theoritical form the research concern with to fin d a specific samples , that lead to the research subject also it includes to points , the first deals with functional view, the other with material for the interior spaces the second concern with functional needs for information space limits ,and the samples used in analyze process.The third chapter: includes the research procedures , which depends on scientifical program in analyze , the ment choice for two samples only from the hole research represented by the research tool by using the list of the spesific analysing doints plus the description and conclusions at the end of the research.chapter four :concern with results and conclusions of the research also the general suggeerstion and recommendations ,this research includes a plan for each sample and clarification pictures and describe methods